The Effect of the Bioactive Compound Curcumin on Conditions After Ischemic Stroke: A Systematic Review - Juliasih, Ni Njoman; Dominikus Raditya Atmaka; Minarni Wartiningsih; Ade Lia Ramadani (Universitas Airlangga, 2024)
Ischemic stroke is a common degenerative disease in Indonesia caused by interrupted or restricted blood supply to part of brain, preventing it from getting oxygen and nutrients. Without sufficient blood supply, brain cells begin to die. Various treatments for ischemic stroke patients have been developed and implemented, but are still ineffective in treating or preventing brain damage. Curcumin is one of the bioactive compounds which mostly found in turmeric which is one of the main spices resource in Indonesia that has many benefits as a medicine. People have been making use of curcumin as a medicine for various diseases, one of which is stroke. Therefore, this systematic review analysed qualitatively the effect of curcumin on the brain condition after ischemic stroke. The method used in this study was a systematic review of 8 databases in the last 10 years, from 2012 to August 2022. Study included was only experimental study on rats. Based on 19 articles gathered, there was a decrement in ROS, COX-2, iNOS, NF-kB, TNF-α, IL-6, Bax, Caspase-9, Caspase-3, ICAM-1, MMP-9, neurological deficit score, and an increment in BCL-2, glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CAT) in rats receiving curcumin intervention either orally or intravenously. Curcumin affects the ischemic brain in a number of ways, namely as an antioxidant, anti-inflammatory, anti-apoptotic, Blood-Brain-Barrier (BBB) protector, increasing neurogenesis, and reducing neurological deficits. It is concluded that curcumin has an elevating effect in protecting brain condition after an ischemic stroke.